A novel role of VEPH1 in regulating AoSMC phenotypic switching. Issue 12 (27th April 2020) - Shi, Xiaofeng; Xu, Caiming; Li, Yongqi; Wang, Han; Ma, Wei; Tian, Yu; Yang, Haifeng; Li, Lei
Abstract: Abdominal aortic aneurysm (AAA) is a potentially lethal disease featured by focal dilatation in the aorta. The transition of vascular smooth muscle cells (SMCs) from a contractile/differentiated to a synthetic/dedifferentiated phenotype is considered to contribute to AAA formation and expansion. Our previous gene microarray data showed that Ventricular Zone Expressed PH Domain Containing 1 (VEPH1) expression increased in angiotensin II (Ang II)‐infused aortic tissues. This study was thus performed to further explore the role of VEPH1. Herein, we first demonstrate that VEPH1 increases in the SMCs of Ang II‐treated abdominal aortas. As in vivo, Ang II also upregulated VEPH1 expression in cultured hAoSMCs. The dedifferentiation of human aortic SMCs (hAoSMCs) was induced by a 24‐hr stimulation of Ang II (1 μM)—the expression of contractile SMC markers, MYH11 and α‐smooth muscle actin (α‐SMA) decreased and that of synthetic markers, proliferating cell nuclear antigen and Vimentin increased. Inhibition of VEPH1 prevented Ang II‐induced pathological dedifferentiation of hAoSMCs as indicated by the restored expression of MYH11 and α‐SMA. In contrast, the forced overexpression of VEPH1 aggravated Ang II's effects. Furthermore, we demonstrated that VEPH1 and transforming growth factor‐β1 (TGF‐β1), a key regulator responsible for vascular SMC differentiation, negatively regulated each other's transcription. In contrast to VEPH1 silencing, its overexpression inhibited recombinant TGF‐β1‐induced increases in MYH11 and α‐SMA and suppressed Smad3 phosphorylation and nuclear accumulation. Collectively, our study demonstrates that VEPH1 elevation promotes the synthetic phenotype switching of AoSMCs and suppressed the TGF‐β1/Smad3 signaling pathway. Identification of VEPH1 as a pathogenic molecule for AAA formation provides novel insights into this disease. Abstract : Ventricular Zone Expressed PH Domain Containing 1 (VEPH1) inhibits the differentiation of aortic smooth muscle cells (AoSMCs).